The View From Within: A Personal Reflection on Library Strategy Development in Three Academic Libraries. Issue 3 (2nd October 2018) - Wales, Tim
ABSTRACT: This article draws on the author's previous experiences of developing library strategies at three case study libraries between 2011 and 2016 across a range of different academic institution types: research-intensive, teaching-intensive, and scientific research. Adopting a reflection on practice methodology based on Gibbs' reflective cycle, the author provides a personal self-assessment of the challenges and opportunities he faced with particular emphasis on locational factors and user feedback. Finally, he concludes with general reflections on library status and recruitment in light of Baker & Allden's leadership research for SCONUL.